Biological evaluation of Black pepper and Eucalyptus extracts and their synergistic activity with chitosan polymer against larvae and adults of southern cowpea beetle Callosobruchus maculatus (Fabricius) under laboratory condition - Iqbal Zhou Abd KashmarL - Mushtak Talib Mohammadali ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The aim of the study was to evaluate the efficiency of plant extracts from oils of black pepper fruits Piper nigrum and Eucalyptus camaldulensis  and the synergistic activity of chitosan polymers with plant extracts against larvae and  adults of the southern cowpea beetle, Callosobruchus maculatus, under laboratory conditions. The results show that the essential oil extract of black pepper fruits causes the highest rates of mortality for adult insects at a concentration of 3 ml per liter, achieving a mortality rate of 75.00% compared to the treatment with eucalyptus extract, which achieved a mortality rate of 63.61% after 7 days of treatment. The same concentration achieved the highest mortality rates for the larval stage, with percentages of 82.22 and 68.33%, respectively. The results of the bio evaluation of the synergistic activity of plant extracts with chitosan polymer against the adult showed superiority of black pepper extract + chitosan polymer at a concentration of 2 ml + 1 ml, respectively, in causing the highest mortality rates, achieving an average of 80.00%, compared to eucalyptus extract + chitosan polymer, which achieved 71.66%.